Advances in Neuroergonomics and Cognitive Engineering Proceedings of the AHFE 2018 International Conference on Neuroergonomics and Cognitive Engineering, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida USA - Ayaz, Hasan; Mazur, Lukasz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers a broad perspective on the field of cognitive engineering and neuroergonomics, covering emerging practices and future trends toward the harmonious integration of human operators and computer systems. It presents novel theoretical findings on mental workload and stress, activity theory, human reliability, error and risk, and neuroergonomic measures alike, together with a wealth of cutting-edge applications. Further, the book describes key advances in our understanding of cognitive processes, including mechanisms of perception, memory, reasoning, and motor response, with a special emphasis on their role in interactions between humans and other elements of computer-based systems. Based on the AHFE 2018 affiliated conference on Neuroergonomics and Cognitive Engineering, held on July 21-25, 2018, in Orlando, Florida, USA, it provides readers with a comprehensive overview of the current challenges in cognitive computing and factors influencing human performance. .
Beyond 2020 NextGen compliance: Human factors and cognitive loading issues for commercial and general aviation pilots -- Analysis of alternatives for neural network training techniques in assessing cognitive workload -- Changes in physiological condition in open versus closed eyes -- Cognitive function evaluation of dementia patients using P300 Speller -- Gaze strategies can reveal the impact of source code features on the cognitive load of novice programmers -- Neural correlates of math anxiety of consumer choices on price promotions -- Implementing the horizontal vestibular ocular reflex test while using an eye tracker as an assessment tool for concussions diagnosis -- How does the mobile phone PPI Design affect the visual acuity with the change of viewing distance.
Keywords: Computational intelligence; Cognitive psychology; User interfaces (Computer systems).; Human-computer interaction; Neurosciences; Biomedical engineering; Medical informatics; Computational Intelligence; Cognitive Psychology; User Interfaces and Human Computer Interaction; Neuroscience; Biomedical Engineering and Bioengineering; Health Informatics